Total Body Irradiation–Based Conditioning Regimen Improved the Survival of Adult Patients With T-Cell Lymphoblastic Lymphoma After Allogeneic Peripheral Blood Stem Cell Transplantation. (July 2022) - Niu, Jiahua; Chen, Zhixiao; Gao, Jie; Qiu, Huiying; Wan, Liping; Wang, Ying; Wang, Wenwei; Tong, Yin; Huang, Chongmei; Cai, Yu; Xu, Xiaowei; Zhou, Kun; et al.
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is one of the consolidation modalities for adult patients with T-cell lymphoblastic lymphoma (T-LBL). However, the optimal conditioning regimen needs to be explored. In the present study, 40 patients with T-LBL undergoing allo-HSCT were retrospectively analyzed, including 23/40 (57.5%) with total body irradiation (TBI)–based conditioning regimen and 17/40 (42.5%) with busulfan (BU)-based regimen. TBI–based regimen significantly increased the cumulative incidence (CI) of grade II to IV acute graft-versus-host disease (aGvHD) as compared with BU-based regimen (13.0% vs 0%, P = 0.000). The relapse risk was significantly lowered in TBI-based group with a 2-year CI of relapse (CIR) of 9.1% as compared with that of 49.6% in BU-based group ( P = 0.008). The 1-year and 2-year non-relapse mortalities (NRMs) for all patients were 5.0% and 10.3%, respectively. The 1-year and 2-year NRMs were 8.9% and 16.0% in TBI-based group, and 0.00% and 0.00% in BU-based group ( P = 0.140). The 2-year probabilities of overall survival (OS) and relapse-free survival (RFS) were 83.0% [95% confidence interval, 63.4%–100%] and 74.0% (95% confidence interval, 54.4%–93.6%) in TBI-based group, which were higher than that of 35.0% (95% confidence interval, 0.0%–72.2%) and 50.0% (95% confidence interval, 24.5%–75.4%) in BU-based group, respectively ( P = 0.020 for OS and P = 0.081 for RFS). In multivariate analysis, TBI-based regimen significantly reduced the risk of relapse [subdistribution hazard ratio (SHR) = 0.030, 95% CI, 0.002–0.040, P = 0.000] and improved the OS [hazard ratio (HR) 0.121, 95% CI, 0.021–0.683, P = 0.017] as an independent prognostic factor. These results suggested that TBI-based regimen might be an optimal choice for adult patients with T-LBL undergoing allo-HSCT.